Auditory P300 as a Neurophysiological Correlate of Symptomatic Improvement by Transcranial Direct Current Stimulation in Patients With Schizophrenia: A Pilot Study. (July 2020) - Kim, Minah; Lee, Tak Hyung; Hwang, Wu Jeong; Lee, Tae Young; Kwon, Jun Soo
Background . The reduced amplitude, prolonged latency, and increased intertrial variability of auditory P300 have been consistently reported in relation to the symptomatic severity of schizophrenia. This study investigated whether auditory P300 event-related potentials can be used as an objective indicator of symptomatic improvement by transcranial direct current stimulation (tDCS) in patients with schizophrenia. Methods . Ten patients with schizophrenia received 20 minutes of 2-mA tDCS twice a day for 5 consecutive weekdays. The anode was placed over the left dorsolateral prefrontal cortex, and the cathode was placed over the left temporo-parietal cortex. The Positive and Negative Syndrome Scale (PANSS) and the auditory P300 were measured for each participant at baseline and after the completion of the tDCS applications. Results . The participants showed significant improvement in the positive and negative symptoms as indexed by change in the PANSS scores by the tDCS. The P300 amplitude, latency, and intertrial variability did not statistically significantly differ after the tDCS application. However, a significant association was observed between the reduced P300 intertrial variability and improvement in the positive symptoms by tDCS. In addition, the changes in both the P300 latency and intertrial variability were significantly correlated with reduced negative symptoms after the tDCS application. Conclusions . Although this pilot study is limited by the small sample size and lack of a sham control, the results suggest that auditory P300 may be a putative marker reflecting the effect of tDCS on the positive and negative symptoms of schizophrenia.